2023
DOI: 10.1097/ijg.0000000000002325
|View full text |Cite
|
Sign up to set email alerts
|

Preserflo MicroShunt: Efficacy and Endothelial Cell Density

Friedrich Anton Steindor,
Céline Trigaux,
Christoph Holtmann
et al.

Abstract: Précis: A main safety concern associated with new glaucoma implants is corneal endothelial cell loss, which could even be observed in already established procedures. Purpose: The purpose of this study was to evaluate the efficacy and corneal safety, especially corneal endothelial cell loss (ECL), after Preserflo MicroShunt implantation. Methods: A monocentric, prospective clinical observational study of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similarly, Qidwai et al [17] found no significant ECL over a 24-month study period; however, endothelial cell counts were available for only 12 of 48 patients. Furthermore, studies by Jamke et al [18] and by Steindor et al [19] found no significant ECL 12 months after PMS implantation. Notably, however, the current study is the only one investigating the impact of the PMS on the corneal endothelium with a follow-up period of at least 2 years.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Qidwai et al [17] found no significant ECL over a 24-month study period; however, endothelial cell counts were available for only 12 of 48 patients. Furthermore, studies by Jamke et al [18] and by Steindor et al [19] found no significant ECL 12 months after PMS implantation. Notably, however, the current study is the only one investigating the impact of the PMS on the corneal endothelium with a follow-up period of at least 2 years.…”
Section: Discussionmentioning
confidence: 93%
“…In a post hoc analysis of 5-year data for Hydrus, CyPass, and iStent inject procedures compared to phakoemulsification alone, it could be shown that the iStent had the lowest impact on ECD with the Hydrus and CyPass implants showing higher (and, in case of CyPass, accelerating) ECD loss [24]. The Preserflo MicroShunt implant similarly showed some ECD loss in most studies, with the position of the inflow end in relation to the corneal endothelium being of particular importance [25,26].…”
Section: Intervention Iop-reduction [Mmhg]mentioning
confidence: 95%